Deliberative practices in and outside the Malaysian parliament - Nazli Aziz (New Zealand: University of Auckland, 2014)
This study is structured as a case study analysis that explores the parliament-citizen relationship of the Malaysian Parliament from the eighth to the twelfth parliaments (October 1990 - March 2013). The Malaysian Parliament is used as a case to understand the deliberative practices of a Westminster-style parliament in an illiberal democracy. This study makes a contribution to the literature by filling the apparent gap and contributing to an understanding of the extent to which the Malaysian Parliament incorporate deliberation as a means of involving their citizens in the policy-making process.